There was a cold lady who swallowed some snow! - Colandro, Lucille; Lee, Jared D. (New York Scholastic, 2003)
In this variation on the traditional cumulative rhyme, a woman swallows some snow, a pipe, some coal, a hat, a stick, and a scarf.
2.
Keywords: Folk songs, English -- Texts; Folk songs; Nonsense verses